Exploring the potential of hematite as a debromination agent for 2,4,6-tribromophenol - Nada A. Mousa; Labeeb Ali; Mohamed S. Kuttiyathil; Hussein A. Mousa; Mohammednoor Altarawneh (Chemical Engineering Journal Advances, 2022)
2,4,6-tribromophenol (TBP) signifies the most widely produced bromophenols with a direct application as a brominated flame retardant (BFRs). Bromophenols also arise as a major product from thermal degradation of various BFRs. Co-pyrolysis of BFRs with metal oxides represent a viable approach in the chemical recycling of polymers laden with bromine, in a process that aims to reduce or eliminate brominated species. However, most literature studies have focused on the degradation of tetrabromobisphenol A (TBBA) in particular. This work investigates – via a wide array of techniques- co-pyrolysis of TBP with a notable metal oxide; namely hematite (Fe2O3). Hematite exhibits a good debromination capacity via reducing emission of HBr from degradation of neat TBP by 45% when a 1:1 mixing ratio is considered. Deploying various mixing ratios does not alter the apparent degradation steps. Between 150 and 500 °C, Fe2O3-assited conversion of TBP reaches ∼ 33%. Analysis of evolved products in the oil fraction reveals the formation of several non-brominated species, nonetheless, unreacted TBP dominate the profile of products. However, no brominated compounds are observed in the gaseous fraction where most products feature alkylated benzenes. XRD and SEM-EDX analysis of the solid residue confirms bromine's fixation by hematite. Conversion of hematite into FeBr3, and consequently FeBr2, ensues via dissociative uptake of HBr followed by a water elimination. Addition of hematite reduces the activation energy for the degradation process in reference to neat TBP. Outcomes reported herein shall be useful in further exploring the effectiveness of iron oxides species as debromination agents of BFRs.